Microbiome-Metabolomics Analysis Investigating the Impacts of Dietary Starch Types on the Composition and Metabolism of Colonic Microbiota in Finishing Pigs - Yu, Miao; Li, Zhenming; Chen, Weidong; Rong, Ting; Wang, Gang; Ma, Xianyong (Frontiers in Microbiology, 2019)
The present study used a combination of 16S rRNA MiSeq sequencing strategy and gas chromatograph time of flight mass spectrometer (GC-TOF/MS) technique to investigate the effects of starch sources on the colonic microbiota and their metabolites in finishing pigs. A total of 72 crossbred barrows were allocated to three different experimental diets with eight replicates and three pigs per replicate. The diet types included tapioca starch (TS), corn starch (CS), and pea starch (PS) (amylose/amylopectin were 0.11, 0.25, and 0.44, respectively). Results showed that the PS diet markedly increased (adjusted P < 0.05) the abundance of short-chain fatty acids (SCFAs) and lactate producers, such as Lactobacillus, Prevotella, Faecalibacterium, and Megasphaera, and decreased (adjusted P < 0.05) the abundance of Escherichia coli when compared with the TS diet. The metabolomic and biochemistry analyses demonstrated that the PS diet increased (adjusted P < 0.05) the concentrations of organic acids (acetate, propionate, butyrate, valerate, and lactate) and some macronutrients (sugars and long-chain fatty acids), and decreased (adjusted P < 0.05) the amino acids and their derivatives (leucine, glycine, putrescine, cadaverine, skatole, indole, and phenol) when compared with the TS diet. Additionally, Spearman’s correlation analysis revealed that the changes in the colonic metabolites were associated with changes in the bacterial composition. Correlatively, these findings demonstrated that the different dietary starch types treatment significantly altered the intestinal microbiota and metabolite profiles of the pigs, and dietary with higher amylose may offer potential benefits for gut health.